PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PASIEN PADA PUSKESMAS KAMONJI DI KOTA PALU - PUTRI, AGFINIA HARDIYANTI (Fakultas Ekonomi Universitas Tadulako, 2017)
The purpose of this study is to determine the effect of service quality consisting of physical evidence, reliability, responsiveness, assurance and empathy on patient satisfaction at the Puskesmas Kamonji in Palu. The sample used is 90 respondents, with sampling technique used is purposive sampling. Data analysis method used in this research is Multiple Linear Regression. The results showed that the service quality variable consisting of physical evidence, reliability, responsiveness, assurance and empathy simultaneously had a significant effect on patient satisfaction at Kamonji Puskesmas in Palu. While partially physical proof, kahandalan, responsiveness, assurance and empathy also have a significant effect on patient satisfaction at Puskesmas Kamonji in Palu.